Biostial iatrogenic coronary artery stenosis: a rare complication of aortic valve surgery successfully treated with percutaneous coronary stenting. (28th January 2019) - Nazir, Sheraz A; Sarfraz, Sanaa; Krishnamoorthy, Suresh; Tapp, Luke
Abstract: A 66-year-old woman presented 4 months after conventional surgical aortic valve replacement with an acute coronary syndrome resulting from rare iatrogenic biostial left main and right coronary artery stenoses, which were successfully treated with percutaneous coronary stenting, optimized by intracoronary imaging.